ACE2: The Major Cell Entry Receptor for SARS-CoV-2 - Scialo, Filippo (Lung, 2020)
Despite the unprecedented effort of the scientific community, the novel SARS-CoV-2 virus has infected more than 46 million people worldwide, killing over one million two hundred thousand. Understanding the mechanisms by which some individuals are more susceptible to SARS-CoV-2 infection and why a subgroup of them are prone to experience severe pneumonia, and death should lead to a better approach and more effective treatments for COVID-19. Here, we focus our attention on ACE2, a primary receptor of SARS-CoV-2. We will discuss its biology, tissue expression, and post-translational regulation that determine its potential to be employed by SARS-CoV-2 for cell entry. Particular attention will be given to how the ACE2 soluble form can have a great impact on disease progression and thus be used in a potential therapeutic strategy. Furthermore, we will discuss repercussions that SARS-CoV-2/ACE2 binding has on the renin–angiotensin system and beyond. Indeed, although mostly neglected, ACE2 can also act on [des-Arg 937]-bradykinin of the kinin–kallikrein system regulating coagulation and inflammation. Thorough comprehension of the role that ACE2 plays in different pathways will be the key to assess the impact that SARS-CoV-2/ACE2 binding has on organismal physiology and will help us to find better therapies and diagnostic tools.